Factors Contributing to Exacerbating Vulnerabilities in Global Clinical Trials - Silva, Ricardo E. da; Amato, Angélica A.; Guilhem, Dirce B.; Carvalho, Marta R. de; Lima, Elisangela da C.; Novaes, Maria Rita C. G. (Frontiers in Pharmacology, 2018)
Background: Although policies and guidelines make use of the concept of vulnerability, few define it. The European Union’s directive for clinical trials does not include explanations for or the reasoning behind the designation of certain groups as vulnerable. Emerging economies from lower middle income countries have, in recent years, had the largest average annual growth rate, as well as increase, in number of clinical trials registered in the US government’s database. Nevertheless, careful supervision of research activities has to be ensured. Objective: To de-scribe and analyze the features of the clinical trials involving vulnerable populations in various countries classified by development status and geographic region. Methods: Retrospective study that involved analysis of data obtained from the International Clinical Trials Registry Plat-form (ICTRP) database between 01/2014 and 12/2014 from countries with (i) highest trial den-sities during 2005 to 2012, (ii) highest average growth rate in clinical trials, and (iii) greatest trial capabilities. Results: Statistical analysis of this study showed that patients incapable of giving consent personally are 11.4 times more likely to be vulnerable patients than patients who are capable, and that patients in upper-middle-income countries are 1.7 times more likely to be vulnerable patients than patients from high-income countries when participating in global clini-cal trials. Malaysia (21%), Egypt (20%), Turkey (19%), Israel (18%) and Brazil (17%) had the highest percentages of vulnerable populations involving children. Conclusions: Although the inability to provide consent personally was a factor associated with vulnerability, arbitrary crite-ria may have been considered when classifying the populations of clinical trials as vulnerable. The EU Clinical Trials Register should provide guidance regarding exactly what aspects or fac-tors should be taken into account to frame given populations as vulnerable, because vulnerabil-ity is not applicable to all risk situations.